2015
DOI: 10.1371/journal.pone.0137717
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Microbiome of Denture Wearers Is Influenced by Levels of Natural Dentition

Abstract: ObjectivesThe composition of dental plaque has been well defined, whereas currently there is limited understanding of the composition of denture plaque and how it directly influences denture related stomatitis (DS). The aims of this study were to compare the microbiomes of denture wearers, and to understand the implications of these towards inter-kingdom and host-pathogen interactions within the oral cavity.MethodsSwab samples were obtained from 123 participants wearing either a complete or partial denture; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
3
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 59 publications
5
93
3
14
Order By: Relevance
“…Similar to our results, a recent sequencing study (12) and older culture-based approaches (11, 16, 24) found no difference in the apparent microbial composition between healthy and stomatitis patients and noted only that the amount of plaque buildup is significantly greater in stomatitis patients. In contrast, a clone library-based culture-independent study (10) reported that the microbiota of biofilms colonizing dentures in health and disease are distinct.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our results, a recent sequencing study (12) and older culture-based approaches (11, 16, 24) found no difference in the apparent microbial composition between healthy and stomatitis patients and noted only that the amount of plaque buildup is significantly greater in stomatitis patients. In contrast, a clone library-based culture-independent study (10) reported that the microbiota of biofilms colonizing dentures in health and disease are distinct.…”
Section: Discussionsupporting
confidence: 92%
“…A detailed clone library analysis (10) provided a first glimpse into the diversity of bacterial phylotypes associated with dentures in health and disease, while a recent predominantly class and phylum level study (12) introduced modern sequencing approaches to the field. The data presented here comprise the first comprehensive genus and species level analysis of the bacteria residing in biofilms on the dentures and remaining teeth of healthy patients and those with stomatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a positive correlation between the absolute candidal numbers and disease was observed, suggesting that the physical interaction between large numbers of yeasts and hyphae on the denture surface was more important than the phenotype per se. This is likely influenced by the diverse microbiota in this environment, which we have recently described (22). Indeed, there is increasing evidence that Candida and bacteria form polymicrobial biofilms, and that some bacterial species common to the oral cavity can enhance the pathogenicity of C. albicans (35)(36)(37)(38), and that the presence of specific oral bacteria is enough to transform a C. albicans LBF into a HBF (39).…”
Section: Discussionmentioning
confidence: 83%
“…Samples for this study were obtained from 129 denture wearers attending the Glasgow Dental Hospital and School for routine treatment, as previously described by our group (22). Written informed consent was obtained from all participants.…”
Section: Patient Samplingmentioning
confidence: 99%